2004
DOI: 10.1152/japplphysiol.00645.2004
|View full text |Cite
|
Sign up to set email alerts
|

Effects on breathing of focal acidosis at multiple medullary raphe sites in awake goats

Abstract: To gain insight into why there are chemoreceptors at widespread sites in the brain, mircrotubules were chronically implanted at two or three sites in the medullary raphe nuclei of adult goats (n = 7). After >2 wk, microdialysis (MD) probes were inserted into the microtubules to create focal acidosis (FA) in the awake state using mock cerebral spinal fluid (mCSF) equilibrated with 6.4% (pH = 7.3), 50% (pH = 6.5), or 80% CO(2) (pH = 6.3), where MD with 50 and 80% CO(2) reduces tissue pH by 0.1 and 0.18 pH unit, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

5
60
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 67 publications
(65 citation statements)
references
References 34 publications
(37 reference statements)
5
60
0
Order By: Relevance
“…Electrophysiological recordings of in vitro preparations have shown that neurons in the retrotrapezoid nucleus, nucleus of the solitary tract, the medullary raphe nucleus (MRN), locus coeruleus, and the pre-Bötzinger complex (preBötzC) increase discharge frequency when the pH in the bathing solution is reduced (3,5,8,14,22,24). Studies in anesthetized preparations that either created a focal acidosis (FA) or assessed the effects of lesions on the hypercapnic ventilatory response also support the concept of widespread chemosensitivity in the medulla, pons, and cerebellum (11,18,32,33,35,36,37).While the in vivo data, under physiological conditions, suggest that chemoreceptors at multiple sites influence breathing, the observed ventilatory effects are not uniform, and the hyperpnea is small, with FA at a single site compared with the hyperpnea observed during a global brain acidosis. In the awake goat, microdialyzing (MD) hypercapnic mock cerebral spinal fluid (mCSF), which decreases extracellular fluid (ECF) pH by 0.018 in one area of the MRN, increases pulmonary ventilation (V I) by 12% (10), while a comparable global brain acidosis resulting from 2.5% inspired CO 2 increases breathing by 100% (10).…”
mentioning
confidence: 91%
See 4 more Smart Citations
“…Electrophysiological recordings of in vitro preparations have shown that neurons in the retrotrapezoid nucleus, nucleus of the solitary tract, the medullary raphe nucleus (MRN), locus coeruleus, and the pre-Bötzinger complex (preBötzC) increase discharge frequency when the pH in the bathing solution is reduced (3,5,8,14,22,24). Studies in anesthetized preparations that either created a focal acidosis (FA) or assessed the effects of lesions on the hypercapnic ventilatory response also support the concept of widespread chemosensitivity in the medulla, pons, and cerebellum (11,18,32,33,35,36,37).While the in vivo data, under physiological conditions, suggest that chemoreceptors at multiple sites influence breathing, the observed ventilatory effects are not uniform, and the hyperpnea is small, with FA at a single site compared with the hyperpnea observed during a global brain acidosis. In the awake goat, microdialyzing (MD) hypercapnic mock cerebral spinal fluid (mCSF), which decreases extracellular fluid (ECF) pH by 0.018 in one area of the MRN, increases pulmonary ventilation (V I) by 12% (10), while a comparable global brain acidosis resulting from 2.5% inspired CO 2 increases breathing by 100% (10).…”
mentioning
confidence: 91%
“…Electrophysiological recordings of in vitro preparations have shown that neurons in the retrotrapezoid nucleus, nucleus of the solitary tract, the medullary raphe nucleus (MRN), locus coeruleus, and the pre-Bötzinger complex (preBötzC) increase discharge frequency when the pH in the bathing solution is reduced (3,5,8,14,22,24). Studies in anesthetized preparations that either created a focal acidosis (FA) or assessed the effects of lesions on the hypercapnic ventilatory response also support the concept of widespread chemosensitivity in the medulla, pons, and cerebellum (11,18,32,33,35,36,37).…”
mentioning
confidence: 91%
See 3 more Smart Citations